1980
DOI: 10.1128/iai.29.2.401-407.1980
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to pathogenic free-living amoebae: role of humoral antibody

Abstract: Pathogenic free-living amoebae are common in nature, but few clinical infections by these amoebae have been reported. This has prompted studies of host susceptibility factors in humans. A survey of normal human sera from three New Zealand Health Districts was made; antibodies to pathogenic free-living amoebae were found in all sera, with titers ranging from 1:5 to 1:20 for Naegleria spp. and from 1:20 to 1:80 for Acanthamoeba spp. The antibodies belonged mainly to immunoglobulin G and immunoglobulin M classes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…These studies showed that specific antibodies can be demonstrated in PAM and GAE patients, and that cross-reactivity between FLA infections is limited [87,93,95]. In addition, these studies showed that the sera of healthy volunteers demonstrate some reactivity and if the reactivity in the sera of healthy volunteers against the three FLA are compared, it seems that most reactivity is found against Balamuthia and Acanthamoeba, which could suggest that contact with those FLA occurs more frequently than with N. fowleri [89,93,95]. However, it is questionable whether an observed low reactivity is specific and really reflects previous exposure or a past infection.…”
Section: Trends Trends In In Parasitology Parasitologymentioning
confidence: 95%
See 1 more Smart Citation
“…These studies showed that specific antibodies can be demonstrated in PAM and GAE patients, and that cross-reactivity between FLA infections is limited [87,93,95]. In addition, these studies showed that the sera of healthy volunteers demonstrate some reactivity and if the reactivity in the sera of healthy volunteers against the three FLA are compared, it seems that most reactivity is found against Balamuthia and Acanthamoeba, which could suggest that contact with those FLA occurs more frequently than with N. fowleri [89,93,95]. However, it is questionable whether an observed low reactivity is specific and really reflects previous exposure or a past infection.…”
Section: Trends Trends In In Parasitology Parasitologymentioning
confidence: 95%
“…The seropositivity rate for B. mandrillaris, which is far less widespread, is low in high-income countries in moderate climates and higher in rural Africa [87,88]. The seropositivity rate of N. fowleri was reported to be very high in the 1980s but more recent data are not available [89][90][91].…”
Section: Comparison Of the Three Amoeba Speciesmentioning
confidence: 99%
“…Acanthamoeba spp. are ubiquitous organisms and consistent with this notion, serological surveys conducted in the past have reported that around 50% to 100% of healthy individuals possessed anti-Acanthamoeba antibodies [9,10]. However, these Acanthamoebaspecific antibodies have limited potential for AK diagnosis.…”
Section: Introductionmentioning
confidence: 92%
“…can trigger responses from the adaptive immune system. Serological surveys reveal that around 90% of adults with no prior Acanthamoeba infections express serum IgG antibodies specific to Acanthamoeba antigens, and 50% of asymptomatic individuals exhibit T-cell responses to Acanthamoeba antigens [53][54][55]. Despite the presence of adaptive immunity, both pigs and Chinese hamsters remain susceptible to Acanthamoeba keratitis (AK), with no evidence suggesting that immunization prevents or alleviates corneal infection.…”
Section: Pathogenesismentioning
confidence: 99%